Achieving Security in Ad hoc Networks Using Identity and Trust with Key Management - Nair, Pranav; Jadhav, Archana; Gunjal, Swapnaja; Gadsing, Ruchita (International Journal of Computer Sciences and Engineering, 2014)
A Network user has to provide susceptible personal information (e.g. name, residence address, credit/debit card number, contact number, driver’s license number and date of birth, etc.) when they are requested by some Web page. This exclusive Personal Identity Information may be used to exclusively identify, contact and/or locate a particular user. This information may be exploited and abused if not properly protected. An Identity Management (IDM) system is therefore proposed to overcome this problem and helps to decide the access to this information in a secure manner. The concept of key management has been implemented to achieve the goal of trusted communication. The group public key management scheme, trust of a node and physical identity helps in secure data transfer over wireless channels through the concept of composite identity and trust based model(CIDT). To validate a node in the network Trust Factor of a node along with its key pair and identity is used. Proposed method works well for self certification scheme of a node in the network.